How Career Identity Shapes the Meaning of Work for Referred Employees - Williams, Lawrence H. (Frontiers in Sociology, 2019)
Sociological explanations for why referred employees typically have longer tenures than nonreferred employees tend to be either that referred employees enter their jobs possessing a clearer sense of employer expectations or that they often receive support from their referrers while on the job. However, through analysis of work-history interviews conducted with salespersons in Toronto, Canada, I find that the significance of each of these factors for a person’s tenure depends on their career plans. For individuals with clear career plans, information mattered but support was less important. Conversely, for individuals with unclear career plans, support mattered but information was less important. I find that this divergence was based on the fact that individuals who had clearer career plans cared more about the fit they had with the tasks they performed jobs which they were referred into while those with unclear plans tended to be more concerned about their overall fit with the job’s culture. I delineate these this difference in job satisfaction by demonstrating how the combination of information and support respondents had at any given job led them to either support, interrogate, or re-route their career plans differently based on the initial clarity of these plans. Based on these findings, I argue that the role that referrals play in shaping turnover intentions should be nested within individuals’ career identities. Doing so prevents researchers from seeing turnover intentions as being solely based on expectations at the time of hire or connections made, strengthened, or weakened on-the-job and, instead, necessitates a more grounded view of turnover decisions.